Patient satisfaction toward doctor communication in medical clinics: a study from northern Sri Lanka - Shanjeeban Ponnuthurai; Suganthan Navaneethakrishnan; Rajeshkannan Nadarajah (Academia Medicine)
A good medical practice involves good communication between the patient and the doctor. Inadequate communication is a significant factor in determining patients’ discontentment and frustration, which ultimately leads to poor healthcare quality. This is an outpatient clinic-based cross-sectional study, conducted among medical clinic patients in northern Sri Lanka. Data were collected systematically from randomly sampled patients. Of 407 patients who participated, the significant proportion (36.4%) were above the age group of 60 and 57.2% were females. The large proportion of patients (33.9%) had completed their tertiary education and most of the participants were unemployed (37.6%) or laborers (20.9%). The majority of patients (96.6%CI: 94.4–98.0%) were satisfied with the doctor communication. However, a significant proportion of patients reported that the doctor did not give time for further questions (44.1%). Furthermore, patients who were unaccompanied to the consultation showed higher satisfaction levels than those who attended with bystanders (P < 0.001). Longer waiting time was negatively associated with patients’ satisfaction levels (P = 0.008). Patients’ trust level regarding doctors was high, with a mean score of 8.82 with SD = 1.44 on a 1–10 scale. Trust-level scores varied significantly with the level of satisfaction regarding doctor communication (P < 0.001). In this study, patients’ satisfaction level regarding doctor communication skills was high. Waiting time and the presence of bystanders during the consultation were negatively associated with respect to satisfaction levels. Furthermore, patient satisfaction can be promoted by reducing the waiting time and addressing bystanders’ concerns.